Designing a Looker Studio-Based Analytics Dashboard for Flight Delay Analysis - Wina Elsa Wardana Wardana (Journal of Computing and Smart Ecosystems, 2025)
The development of digital technology in the Industrial Revolution 4.0 era has encouraged intensive data utilization in various sectors, including the aviation industry. One of the main problems faced by airlines is flight delays, which have a significant impact on operations, costs, and customer satisfaction. This study aims to analyze flight delay patterns using the Flight Delays dataset from Kaggle and to design an interactive dashboard based on Looker Studio to support decision-making. The methods used include data collection, data cleaning, statistical analysis (One-Way ANOVA, linear regression, and Chi-Square test), and data visualization. The results show that there are significant differences in the average delay between airlines, flight distance has a very weak effect on delays, and the airport of origin has a significant relationship with delay occurrences. The resulting dashboard is able to provide comprehensive insights regarding delay factors so that it can be used in optimizing flight operations.